1981
DOI: 10.1152/jappl.1981.51.6.1493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of menstrual cycle on blood lactate, O2 delivery, and performance during exercise

Abstract: The effects of the menstrual cycle on cardiorespiratory variables, blood lactate, and performance were studied in exercising females. Nine healthy subjects, 20--24 yr of age, were investigated in midfollicular and midluteal phases of the menstrual cycle at 33, 66, and 90% of maximum power output (light, heavy, and exhaustive exercise). Occurrence of ovulation was confirmed in all subjects by measurement of progesterone, which increased from 0.6 +/- 0.1 (mean +/- SE) in the follicular to 8.9 +/- 2.2 ng/ml in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
152
7
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(183 citation statements)
references
References 0 publications
20
152
7
4
Order By: Relevance
“…In contrast, some previous studies have observed greater minute ventilation during exercise in the luteal phase compared with the follicular phase, 4,6,9,11,12 but this has not been consistently reported. 2,3,5,8,10 However, despite the finding of no difference in minute ventilation between EF and ML in this current study and no significant correlation between absolute minute ventilation and ovarian hormones, we did observe a significant relationship in the change in minute ventilation from EF to ML and the oestrogen and progesterone concentration, and the magnitude of increase in oestrogen between these menstrual phases.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…In contrast, some previous studies have observed greater minute ventilation during exercise in the luteal phase compared with the follicular phase, 4,6,9,11,12 but this has not been consistently reported. 2,3,5,8,10 However, despite the finding of no difference in minute ventilation between EF and ML in this current study and no significant correlation between absolute minute ventilation and ovarian hormones, we did observe a significant relationship in the change in minute ventilation from EF to ML and the oestrogen and progesterone concentration, and the magnitude of increase in oestrogen between these menstrual phases.…”
Section: Discussioncontrasting
confidence: 59%
“…Most previous studies use only minute ventilation or ventilatory equivalents as a means of comparing respiratory drive during exercise between menstrual phases, [2][3][4][5][6][8][9][10][11][12] and do not consider the contributing variables, respiratory rate or tidal volume. Furthermore, most previous reports have only evaluated ventilatory drive over short exercise periods [3][4][5][6][10][11][12] whereas the current study demonstrated that the increase in respiratory rate during exercise in the ML phase continued to persist throughout a prolonged exercise period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants for this study consisted of 12 trained, competitively active female cyclists (26.661.3 y, 161.086 1.78 cm, 58.6761.74 kg) training an average of 3.9260.64 y. As high-intensity exercise, lactate production, and lactate clearance are negatively affected during the follicular phase (17), all testing took place in the luteal phase of menstruation (48-h after selfreported cessation of menses). Participants completed an initial exercise log and maintained the same level of training intensity, time, and volume for the duration of the study.…”
Section: Methodsmentioning
confidence: 99%